DEVELOPMENT OF CHARACTERISTIC MOTIFS ON PRINTING MASKS AS PROMOTIONAL MEDIA FOR VISUAL CAMPAIGN IN PRODUCT DESIGN STUDY PROGRAM, ESA UNGGUL UNIVERSITY - Putri Anggraeni Widyastuti; Ratih Pertiwi; Huddiansyah Huddiansyah (Gestalt : Jurnal Desain Komunikasi Visual, 2021)
The condition of the covid-19 virus pandemic gave to the term “new normal” lifestyle in society., They must wear a fabric mask who can be produces by digital printing as one of the visual promotional media. Therefore, the product is used as part of the lecture assignments for product design students at Esa Unggul University. It uses the process to development characteristic motifs as a visual material for printing masks. The goal is that they can apply the result of process to include a new visual aesthetic in a product. The applied research method was carried out by involving product design students from Esa Unggul University who were involved in similar course through questionnaire data collection. The result was found that the development creating characteristics motifs to produce new visuals or patterns. It can be used as a promotional media for a visual campaign for a printing mask product. In other words, the development creating process base of human image triangular can be used as experience developing characteristic motifs for designing printing masks. It is suggested to train the sensitive of product design student in visualizing the characteristics of visual campaign printing masks.